Ekranisasi Unsur Intrinsik Novel Antares Karya Rweinda ke Dalam Film Antares yang Disutradarai oleh Rizal Mantovani - Alfianie Alfianie; Patrisia Cuesdeyeni; Alifiah Nurachmana; Albertus Purwaka; Ika Nurfitria (Universitas Palangka Raya, 2022)
This study aims to determine the ecranization of Rweinda's Antares novel into the Antares film directed by Rizal Mantovani, namely in the form of shrinking, adding, and varying changes. This research is limited to ecranization analysis of intrinsic elements (plot, characters, and setting). Therefore, this study will describe: (1) the ecranization of Rweinda's novel Antares in the film Antares directed by Rizal Mantovani, (2) the ecranization of the addition of the novel Antares by Rweinda into the film Antares directed by Rizal Mantovani, and (3) the ecranization of changes varies from the novel Antares by Rweinda to the film Antares directed by Rizal Mantovani. This study used descriptive qualitative method. The subject of this research is a novel entitled Antares by Rweinda and the film Antares directed by Rizal Mantovani. Data collection procedures in this study used reading techniques, viewing techniques, and note-taking techniques.